The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.37287/jppp.v2i4.161
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Effectiveness of Giving Carrot and Red Ginger Juice Against Menstrual Pain in Adolescents

Abstract: Dismenorea merupakan nyeri haid yang di tandai dengan nyeri perut bagian bawah yang terjadi sebelum menstruasi dan saat menstruasi. Dismenorea jika tidak segera diatasi akan mempengaruhi fungsi mental dan fisik individu, sehingga harus segera di atasi dengan terapi farmakologi atau non farmakologis. Terapi non farmakologis yaitu pengobatan herbal seperti air perasan wortel dan air rebusan jahe merah. Wortel memiliki kandungan Beta karoten dan vitamin E yang bisa mengurangi peningkatan produksi hormon prostagla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The results suggested that the NPRS scores of the three groups showed significant differences. In accordance with prior research, which suggested dark chocolate ( 11 ), and carrot juice ( 15 , 16 ) as a non-pharmaceutical, effective, and easy-to-use strategy for menstrual pain management, these data supported these recommendations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results suggested that the NPRS scores of the three groups showed significant differences. In accordance with prior research, which suggested dark chocolate ( 11 ), and carrot juice ( 15 , 16 ) as a non-pharmaceutical, effective, and easy-to-use strategy for menstrual pain management, these data supported these recommendations.…”
Section: Discussionsupporting
confidence: 85%
“…A randomized clinical trial among labor women suggested that who had consumption phenolics significantly decreased pain intensity ( 14 ). Several studies have investigated the effect of carrot juice on declining severe pain in menstruation ( 15 , 16 ), but no of study to investigate the effect of carrot juice on pain at the first stage of labor.…”
Section: Introductionmentioning
confidence: 99%
“…However, some students and their families opted for traditional medicine, as it is widely trusted in the community [6], [9]. Traditional medicine services are abundant in the area, and it is commonly believed to be effective in treating various ailments [10].…”
Section: Introductionmentioning
confidence: 99%